Fiqh education for adolescent girls: Study of the latanun nisa in temanggung, indonesia - Laeli Aulia Ifani; Muhammad Chafidz Ali; Sigit Tri Utomo; Ana Sofiyatul Azizah (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
Many adolescent girls in Brongkol Village lack understanding regarding the distinction between menstrual bleeding (haid) and abnormal vaginal bleeding (istihadhah), crucial aspects of the fiqh of worship governing Muslim women's daily lives. This study aims to explore the urgency, implications, advantages, and disadvantages of women's fiqh education through the Ianatun Nisa book among adolescent girls in Brongkol Village, Temanggung Sub-District. Conducted as field research, this qualitative study adopts a phenomenological approach, gathering data through interviews, observations, and documentation. Data analysis involves collection, reduction, presentation, and conclusion drawing, with data validity ensured through source triangulation. Findings indicate the significance of women's fiqh education for adolescent girls in Brongkol Village. Studying menstrual bleeding (haid) and abnormal vaginal bleeding (istihadhah) is obligatory, impacting their daily worship practices like prayer and fasting. Positive impacts include improved understanding through expository and reflective approaches, facilitated by lecture and discussion methods. However, challenges such as limited Arabic pegon Javanese script literacy among adolescent girls and methodological constraints hinder effective implementation.